Maxillary sinusitis as a complication of infected dens invaginatus in maxillary lateral incisor: A case report - Paras Mull Gehlot; Vinutha Manjunath; Mysore Krishnaswamy Manjunath (Wolters Kluwer Medknow Publications, 2015)
Introduction: Maxillary sinusitis can have various origins, including odontogenic origin. Case Report: We describe a case of maxillary sinusitis in a 25-year-old female patient who experienced pain and swelling in the right maxillary region as a complication of infected maxillary lateral incisor. Clinical and radiographic examinations revealed dens invaginatus (DI; Oehler's type III) associated with apical pathosis in the maxillary right lateral incisor, with a large periapical lesion involving the adjacent four teeth. Nonsurgical root canal treatment using calcium hydroxide medicament was carried out for all five teeth, which resulted in gradual diminution of sinusitis, and the patient remained asymptomatic. Discussion: This paper emphasizes the following: (i) the challenges posed by DI for root canal treatment because of its anatomical complexity; (ii) a nonsurgical approach in the management of a large periapical lesion, using calcium hydroxide medicament; and (iii) the interdisciplinary management of conditions of common clinical concern for medical and dental practitioners, for successful outcome.